Comparative effectiveness and safety of vancomycin versus linezolid for the treatment of central nervous system infections: a meta-analysis - Zhou, Liujun; Yao, Qihui; Wang, Zecheng; Yu, Lingyan; Yu, Zhenwei; Zhao, Yuhua (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectivesThis study conducted a meta-analysis comparing vancomycin and linezolid for treating central nervous system (CNS) infections, addressing the lack of comprehensive evaluations in existing research on antibiotic therapy for CNS infections.MethodsWe systematically searched databases, including the PubMed, Embase, Web of Science, Cochrane Library and Chinese databases, up to April 22, 2025. All eligible randomized controlled trials and cohort studies of vancomycin or linezolid were included. The clinical success rate was the primary outcome of interest. The secondary outcomes of interest were cerebrospinal fluid (CSF) parameters, systemic inflammatory markers and the occurrence of adverse drug reactions (ADRs). Two reviewers independently extracted the data and assessed the study quality (NOS/ROB 2.0). The meta-analysis employed random/fixed-effects models to calculate pooled dichotomous outcomes (ORs) and continuous outcomes (SMDs) with 95% CIs via RevMan 5.4.ResultsThis meta-analysis included 17 studies (6 head-to-head). Clinical cure rates were not significantly different between vancomycin (84.7%, 222/262) and linezolid (79.7%, 200/251), with a pooled OR of 1.29 (95% CI: 0.55–2.99; p =0.56), while substantial heterogeneity existed (I2 = 58%). The secondary outcomes showed no differences but suffered extreme heterogeneity (I² >90%). Safety analysis revealed a significantly greater ADR with vancomycin (21.0% vs. 15.1%; OR 1.63, 95% CI: 1.01–2.65; p = 0.05) with low heterogeneity (I² = 15%).ConclusionVancomycin and linezolid have similar effectiveness in CNS infection from current available evidences, but vancomycin is associated with a greater risk of ADR. Treatment selection should be based on patients’ individual characteristics, such as risk of thrombocytopenia, renal function, and availability of therapeutic drug monitoring.